Advancement in Biodegradable Equipment for Flexible and Sustainable Electronics - Mehfooz Khan; Dr. Arun Kumar Yadav (International Journal of Electro-Mechanics and Material Behaviour, 2025)
Biodegradable electronics are a quickly developing area focused on reducing the environmental impact of traditional electronic waste by using materials that can break down naturally after use. These devices use eco-friendly polymers, nanocomposites, and bio-based materials that maintain electrical function temporarily before safely decomposing. Recent developments show the potential of plant-based polymers, conductive biodegradable composites, and transient materials that support flexible and wearable applications without causing long-term harm to the environment. These materials have led to the creation of soft sensors, implantable medical tools, and short-term monitoring systems that do not require surgical removal or waste processing. This approach improves both environmental sustainability and user safety. Moreover, nanofibrous structures, electrospun composites, and biodegradable conductive polymers like polypyrrole and polythiophene have improved the mechanical strength and electrical conductivity of temporary electronic systems. However, significant challenges still exist. These include achieving consistent degradation rates, maintaining performance stability during use, and developing effective encapsulation methods that protect devices while allowing for controlled breakdown later. There are ongoing environmental concerns about the potential release of microplastics, acidic byproducts, or harmful residues during the breakdown of materials. This underscores the need for thorough lifecycle assessments of biodegradable materials. Additionally, high production costs and limited scalability compared to traditional electronics hinder widespread adoption. This indicates a need for better green manufacturing methods and more cost-efficient production techniques. Despite these obstacles, the field continues to expand as innovations in green processing, bioresorbable batteries, and self-healing conductors broaden the options for sustainable device design. Biodegradable electronics have great potential for future uses in healthcare, environmental monitoring, smart wearables, and disposable sensing platforms. Ultimately, they can help create a more environmentally responsible technology landscape.
Keywords: Biodegradable Electronics; Environment; Transient Electronics; conductive polymers; flexible devices; medical devices; sustainable materials